PkM. PELATIHAN PENULISAN MODUL AJAR KURIKULUM MERDEKA DI SMA NEGERI 8 DENPASAR BALI - Putu Dessy Fridayanthi; Gusti Ayu Made Puspawati; Ida Ayu Agung Ekasriadi; I Komang Sukendra (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
Training on writing independent curriculum teaching modules aims to provide understanding and skills to teachers in compiling teaching modules that are in accordance with the independent curriculum. Community service carried out by lecturers at PGRI Mahadewa Indonesia University to provide knowledge and skills to teachers in designing teaching modules that are relevant to the Independent Curriculum. The problem faced by teachers at SMA Negeri 8 Denpasar is the difficulty of teachers in creating teaching modules, so one solution that can be provided is training in writing teaching modules in the Independent Curriculum to improve the quality of learning in the school. The activity was attended by 40 teachers who were guided by lecturers from UPMI to provide training and provide an in-depth understanding of the principles of the independent curriculum and how to integrate them into teaching modules. Training participants learn about teaching module development methods that are oriented towards increasing teacher human resources in empowering students by using the application of technology in learning, and measuring student progress comprehensively. After the activity ended, the teachers were able to develop teaching modules creatively, innovatively and effectively to support the achievement of the learning objectives of the independent curriculum. Through PkM activities at SMA Negeri 8 Denpasar, teachers can create teaching modules in the independent curriculum according to the subjects they teach.